Modeling, simulation and analysis of temperature effects on impedance-based SHM applications using finite elements - Gianesini, Bárbara Morais; Ledesma, Nicolás E. Cortez; Antunes, Rothschild Alencastro; Filho, Jozué Vieira [UNESP] (My University, 2017)
Among several different methods for structural health monitoring (SHM), the ones based on electromechanical impedance (EMI) have been received special attention from researchers. EMI based methods use inexpensive piezoelectric transducers, such as PZT (Pblead Zirconate Titanate) patches since they are simple to implement, extremely light, noninvasive, and are able to perform self-actuating and sensing to detect local damage. However, EMI based methods are very sensitive to environmental changes, which affect transducer properties and have hindered its application in real-world structures. The ambient temperature has been cited in the literature as a critical problem for practical EMI based applications. Therefore, in this paper, it is presented an analytical and numerical study to characterize the effect of temperature on PZT transducers applied to SHM. For that, an EMI-based finite element (FE) model was developed using PZFlex® software. Simulated results compared with experimental ones show that the information obtained can be a powerful tool for developing methods to compensate temperature effects on EMI-based SHM systems operating on wide frequency bands. Tests were carried out varying the temperature from - 20°C to + 70°C for a frequency range of 0-300 kHz.